2023
DOI: 10.3390/ijms24021001
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Fecal Microbiota Transplantation in the Treatment of Neurodegenerative Diseases: A Review

Abstract: Neurodegenerative diseases are highly prevalent but poorly understood, and with few treatment options despite decades of intense research, attention has recently shifted toward other mediators of neurological disease that may present future targets for therapeutic research. One such mediator is the gut microbiome, which communicates with the brain through the gut–brain axis and has been implicated in various neurological disorders. Alterations in the gut microbiome have been associated with numerous neurologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 87 publications
0
16
0
1
Order By: Relevance
“…In a review by Varesi et al, numerous promising dietary therapies were systematically reviewed, including the Mediterranean diet, Dietary Approaches to Stop Hypertension (DASH), the Mediterranean-DASH Neurodegenerative Delay Intervention diet, and the ketogenic diet, and intermitting fasting might be a promising protective dietary strategy for dementia ( Park S. et al, 2020 ; Varesi et al, 2022b ). In addition, fecal microbiota transplantation (FMT) is a method of repairing dysbiotic gut by re-cloning the normal microbiota into the “diseased” intestine ( Gupta et al, 2016 ; Matheson and Holsinger, 2023 ). Although promising results such as restoration of microbiota composition, improved cognitive performance, and reduction in amyloid accumulation and tau expression have been observed in mice in several studies that have been reported ( Dodiya et al, 2019 ; Sun et al, 2019 ), current studies in humans remain in the single digits.…”
Section: Potential Targeted Therapies For Gut Microbiomementioning
confidence: 99%
“…In a review by Varesi et al, numerous promising dietary therapies were systematically reviewed, including the Mediterranean diet, Dietary Approaches to Stop Hypertension (DASH), the Mediterranean-DASH Neurodegenerative Delay Intervention diet, and the ketogenic diet, and intermitting fasting might be a promising protective dietary strategy for dementia ( Park S. et al, 2020 ; Varesi et al, 2022b ). In addition, fecal microbiota transplantation (FMT) is a method of repairing dysbiotic gut by re-cloning the normal microbiota into the “diseased” intestine ( Gupta et al, 2016 ; Matheson and Holsinger, 2023 ). Although promising results such as restoration of microbiota composition, improved cognitive performance, and reduction in amyloid accumulation and tau expression have been observed in mice in several studies that have been reported ( Dodiya et al, 2019 ; Sun et al, 2019 ), current studies in humans remain in the single digits.…”
Section: Potential Targeted Therapies For Gut Microbiomementioning
confidence: 99%
“…Previous studies demonstrated that the composition and diversity of the gut microbiota are altered in AD patients compared to cognitively normal controls [76]. However, evidence using AD animal models showed positive effects after treatment with antibiotics, probiotics, diet modification, or after fecal microbiota transplantation [63,77]. Thus, modulation of the gut microbiota could be a possible therapeutic and preventive intervention to alleviate symptoms or slow down the progression of AD [78][79][80].…”
Section: Alzheimer's Diseasementioning
confidence: 99%
“…It is a new strategy to treat diseases related to microbial imbalance by regulating intestinal flora (Figure 5). FMT has been shown to be effective in the treatment of type 2 diabetes mellitus, neurodegenerative diseases, autism spectrum disorder and so on (Wu et al, 2022;Matheson and Holsinger, 2023;Wang et al, 2023). FMT improved the irradiated animal survival rate, increased peripheral blood leukocyte count, and intestinal epithelial integrity, improved the gastrointestinal function, which can safely and effectively improve the symptoms of chronic radiation enteritis patients with intestinal and mucosa damage.…”
Section: Microbial Therapy Of Radiation Enteritismentioning
confidence: 99%